Persepsi pasien gigi tiruan cekat terhadapPemakaian mahkota tiruan sementara - Risqy Amanda, Nabila; Seftiana Indah Sari, Eka; Pragustine, Yenny (Jurnal Kedokteran Gigi Terpadu, 2025)
Background: Teeth play important role in the life of humans. Tooth loss may result in various anatomical, physiological and psychological changes on humans, including loss of self-confidence and  ability to interact socially. The causes of tooth loss generally include deteriorated tooth health and age factor. Fixed dental prosthesis is a solution to replace one lost natural tooth or more teeth and use of preformed temporary crown will keep the aesthetical and mastication function before a definitive crown is completed and placed. Objective: This research aims to explore the patient’s perception regarding the use of preformed temporary crown in fixed dental prosthesis treatment at the Rumah Sakit Gigi dan Mulut Pendidikan Universitas Trisakti. Method: This research is a descriptive observational research with cross sectional design which involved 30 patients at  RSGM-P USAKTI as respondents. Data were collected using google form by the respondents from February to June 2024. Results: Patient’s perception about toothache after cementation of temporary dental prosthesis (90%), difficulties in cleaning temporary dental prosthesis (93,3%), Gingival hemorrhage (90%), Gingival edema (90%), and oral odor (86,6%), majority respondents answered No. In the questions related to better food mastication (90%), speaking better (93,3%), comfort in using preformed temporary crown (90%), preformed temporary crown in predicting the results (90%), and majority of respondents (93.3%) reported increased self-confidence following the placement of fixed dental prostheses. Conclusion:  The patient's perception when wearing a temporary crown is quite good, so it can provide an idea when using a definitive crown in fixed dental prosthesis treatment.